Biblioteca escolar infantil: um estudo das políticas federais às práticas locais em municípios do sudoeste do Paraná - Moreira, Marina (2020)
This study is part of the research line “Educational Policies” of the Graduate Program in Education - Academic Masters Degree - Federal University of Fronteira Sul - Chapecó campus, with a grant provided by FAPESC. It aims to understand how Brazilian educational policies are structured to establish the Early Childhood Education library in municipalities in the southwest of Paraná. To substantiate this thesis we grounded our study on authors who have reflected and researched the theme of the School Library (CAMPELLO, 2002, 2003; MILANESI, 2013; GEHRKE, 2014, 2018; PATTE, 2012; DURBAN ROCA, 2012). The guiding question of the research is: how the Brazilian educational policies are structured to establish Early Childhood Education libraries in cities in the southwest of Paraná? The adopted methodology has a qualitative approach, involving the direct contact of the researcher with its object, therefore, the research was processed and approved by the Ethics Committee on Research with Human Beings at UFFS. For data treatment, we opted to use content analysis, suggested by Bardin (2016). Based on this approach, three major categories of analysis were defined, namely: place, politics, and municipal management. The analyzes indicated that there is legal support for the establishment of school libraries in early childhood education institutions, linked primarily to the areas of education and culture. However, these Federal Government actions are not structured to guarantee the effective presence of school libraries in public institutions. In the course of this research, it became evident that the “Place Children's School Library” is a children's right, and should be required as a guarantee of quality education and democratization of access to cultural goods. Highlighting the autonomy of federated entities, this dissertation sought in the nine municipalities surveyed to consolidate local policies and realized that their actions are focused on the construction of Municipal Education Plans, which, even with the presence of the library in all of them, the municipalities do not encourage its promotion in Early Childhood Education. In general, the managers showed difficulties in conceptualizing the school library, relating it only to the collection, or to the presence of a librarian. However, it is recognized that for the real existence of a “Place Children's School Library”, it is fundamentally necessary to be conceptualized in the subject, collection, space, and intention tetrad. As a palliative measure, municipal managers develop strategies in an attempt to make up for the absence of this pedagogical resource. Therefore, it is known that these attempts, even causing numerous benefits to children, should not be understood as substitutes for school libraries, but rather, as part of the design of an "in motion" children's school library, designed to meet the needs of the child, enabling the development of autonomy and promoting critical thinking.